Transformasi Third Place Berbasis Learning Commons: Analisis Pemanfaatan Library-Cafe di Universitas Muhammadiyah Surakarta - Asri Tata; Imam Mahmudi (Perpustakaan Universitas Riau, 2025)
This study aims to describe the utilization of the Library-Cafe service at the Universitas Muhammadiyah Surakarta (UMS) Library as a supporting facility for students’ learning activities. The Library-Cafe was established as a transformation of the